Background of innovative platform for substitution of quarry water purifying technology; Pollution Research; Vol. 35, iss. 2 - Tyulenev M. A. Maksim Anatoljevich; Zhironkin S. A. Sergey Aleksandrovich; Kolotov K. A. Konstantin Aleksandrovich; Garina E. A. Ekaterina Aleksandrovna (2016, 2016)
Title screen